Derechos de la naturaleza. La avanzada del constitucionalismo social contemporáneo - Alcivar Toala, Mallury Elizabeth (2022)
ABSTRACTThe contribution presented in this research explores the trajectories of constitutionalism in its history, which accompanies the most relevant events of the modern era. The author has set out to highlight the interrelations of social factors, the interests of natural and legal persons, the role of states and political groups and parties, and ideological anchors, as the main elements that lead to constitutional texts being placed in the leading role in the social fabric where they are today. The most novel expressions of constitutionalism are explored, among which the definition and recognition of the rights of nature constitute one of the most novel and important forms of its expression. KEYWORDS: Constitution, political system, law, human rights. RESUMENLa contribución que se presenta incursiona en las trayectorias del constitucionalismo en su historia que acompaña los acontecimientos más relevantes de la era moderna. La autora se ha propuesto como objetivo destacar las interrelaciones de factores sociales, intereses de personas naturales y jurídicas, rol de los estados y de grupos y partidos políticos, anclajes ideológicos, como elementos principales que conducen a colocar los textos constitucionales en el papel protagónico del tejido social donde hoy se encuentran. Se incursiona en las expresiones más novedosas del constitucionalismo entre las que la definición y reconocimiento de los derechos de la naturaleza constituye una de las más novedosas e importantes formas de expresión del mismo. CÓDIGO JEL: D23, B25.